Assessing soil bacterial community response to organophosphate pesticides in agricultural field of Yogyakarta, Java, Indonesia - ANNA RAKHMAWATI; BERNADETTA OCTAVIA; SUHARTINI SUHARTINI; TIEN AMINATUN (Universitas Syiah Kuala, 2023)
Soil contamination by pesticides is one of the world’s most pressing environmental issues. The widespread use of Organophosphate pesticides (OPPs) in agriculture has led to biological diversity changes. The indigenous bacterial community played significant roles in the remediation of soil contaminated with OPPs. This study examines the overall bacterial community composition of three agricultural fields in Yogyakarta, Java, Indonesia, that were exposed to OPPs. The agricultural field was divided into zones near the beach, residential, and mountainous. Sequencing 16S rRNA amplicon fragments used to analyze the soil bacterial community. It was discovered that Proteobacteria, Actinobacteria, and Firmicutes comprised the majority of the bacterial community. In addition, the samples contain a high relative abundance of Bacillus, Bradyrhizobium, Chryseobacterium, Cystobacter, Microvirga, and Burkholderia. The high alpha diversity indexes suggest that the agricultural soil microbiome provides important ecological services and may harbor a wide variety of bacteria and genes with biotechnological applications. The physicochemical soil characteristics are also correlated with the bacterial community structure. The findings can be used to develop bioremediation strategies that employ native microbes to clean and restore agricultural soil contaminated with OPPs.